Operative versus non-operative management of rib fractures in flail chest after cardiopulmonary resuscitation manoeuvres. (3rd February 2022) - Dorn, Patrick; Pfister, Selina; Oberhaensli, Simone; Gioutsos, Konstantinos; Haenggi, Matthias; Kocher, Gregor J
Abstract: OBJECTIVES: Blunt chest trauma after mechanical resuscitation manoeuvres appears to have a significant impact on the often complicated course. Due to a lack of data in the literature, the purpose of this study was to investigate the feasibility and immediate outcome of chest wall stabilization for flail chest in this vulnerable patient population. METHODS: We retrospectively reviewed the medical records of patients after cardiopulmonary resuscitation between January 2014 and December 2018 who were diagnosed with flail chest. We attempted to compare patients after surgery with those after conservative treatment. RESULTS: Of a total of 56 patients with blunt chest trauma after mechanical resuscitation and after coronary angiography, 25 were diagnosed with flail chest. After the exclusion of 2 patients because of an initial decision to palliate, 13 patients after surgical stabilization could be compared with 10 patients after conservative therapy. Although there was no significant difference in the total duration of ventilatory support, there was a significant advantage when the time after stabilization to extubation was compared with the duration of ventilation in the conservative group. The presence of pulmonary contusion, poor Glasgow Coma Scale score or the development of pneumonia negatively affected the outcome, but additional sternal fracture did not. CONCLUSIONS: Surgical stabilization for chest wall instability is well tolerated even by this vulnerable patient population. Our results should be used for further randomized controlled approaches. It is necessary to evaluate the situation with all parameters in an interdisciplinary manner and to decide on a possible surgical therapy at an early stage if possible. Abstract : Rib fractures are common and are diagnosed in up to 39% of patients with blunt chest trauma [1, 2].